Estimation of Plastic and Other Waste Disposed of by Longline and Gillnet Fleets Operating from Cilacap - Berri Miraz Kholipah Rahman; Wazir Mawardi; Muhammad Fedi Alfiadi Sondita; Craig Proctor (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Tuna-fishing boats based at the Cilacap Oceanic Fishing Port are potential contributors to marine debris in the Indian Ocean. Without a quantitative assessment of the types and amount of debris, port management cannot develop a strategy to address this problem. This study estimated the quantities of plastics and cartons disposed of by these fisheries in the Indian Ocean. Data were collected through observations and interviews with boat managers/owners or fishermen in the port, from August to November 2019, to evaluate the boat supplies loaded on board in the port and the waste returned to the port. The marine disposal per fishing trip (the difference between the quantity of supplies taken to sea and the quantity of waste returned to port) was calculated for 89 trips of gillnet and longline boats, for a size range of 20 to 90 GT. There was no at-sea disposal of used engine oil, rice plastic sacks, styrofoam boxes, nor plastic gallon bottles. Other plastics and cartons from consumable packaging were disposed of at sea. The estimates of the plastic waste disposed were 0.8-4.4 kg.boat-1.trip-1 or 2,143-12,024 pieces.boat-1.trip-1 while the estimates of the cartons disposed were 3.5-19.4 kg.boat-1.trip-1 or 203-1,140 pieces.boat-1.trip-1. The study concluded that fishers could easily keep the waste onboard for disposal on return to port. In addition, port management should initiate a system in which the amounts of waste returned to boats returning to port are considered in granting future port clearance to those boats.